2020
DOI: 10.3390/electronics9060991
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Violet Light-Emitting Diodes Based on ZnO/GaN Heterojunction

Abstract: Progress in light-emitting diodes (LEDs) based on ZnO/GaN heterojunctions has run into several obstacles during the last twenty years. While both the energy bandgap and lattice parameter of the two semiconductors are favorable to the development of such devices, other features related to the electrical and structural properties of the GaN layer prevent an efficient radiative recombination. This work illustrates some advances made on ZnO/GaN-based LEDs, by using high-thickness GaN layers for the p-region of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Many groups have reported the * Author to whom any correspondence should be addressed. fabrication of n-ZnO/p-GaN junction based LEDs, where various growth techniques, such as molecular beam epitaxy [3], metalorganic chemical vapour deposition [4], chemical bath deposition [5], RF magnetron sputter [6] and pulsed laser deposition (PLD) [7], are used to grow the ZnO layer. Emission of light in the wavelength range of 390-415 nm has also been observed from these devices [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many groups have reported the * Author to whom any correspondence should be addressed. fabrication of n-ZnO/p-GaN junction based LEDs, where various growth techniques, such as molecular beam epitaxy [3], metalorganic chemical vapour deposition [4], chemical bath deposition [5], RF magnetron sputter [6] and pulsed laser deposition (PLD) [7], are used to grow the ZnO layer. Emission of light in the wavelength range of 390-415 nm has also been observed from these devices [5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…fabrication of n-ZnO/p-GaN junction based LEDs, where various growth techniques, such as molecular beam epitaxy [3], metalorganic chemical vapour deposition [4], chemical bath deposition [5], RF magnetron sputter [6] and pulsed laser deposition (PLD) [7], are used to grow the ZnO layer. Emission of light in the wavelength range of 390-415 nm has also been observed from these devices [5,[8][9][10]. Recently Ai et al [3] and Turko et al [11] have reported UV light emission from n-ZnO/p-GaN heterojunction LEDs that peak at ∼376 nm and 366 nm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the crystalline p-GaN epilayer with the structure matching to the ZnO material becomes a substitution material for hetero-contacting to n-ZnO film. Although the resulting n-ZnO/p-GaN heterojunction diode showed better diode rectification and photo-electric conversion efficiency as compared to the ZnO-based homojunction diode [12][13][14][15][16][17], structural optimization to confine the device active layer in the n-ZnO layer as well as improvement of its crystallinity is still ongoing. For example, Long et al fabricated an MgZnO/ZnO/MgZnO double heterojunction (DH) structure on the p-GaN epilayer layer using a radio frequency (rf) magnetron sputtering system to confine the injection carriers in the ZnO layer.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its non-toxicity, abundance, and availability in the earth, ZnO is considered very attractive in various technological fields. Moreover, the optical and electrical properties of ZnO and AZO thin films, strongly dependent on the specific growth technique and the processing conditions, make them appealing for many optical, electronic and optoelectronic applications such as transparent and conductive windows [11], memristors [12,13], photocatalysis [14][15][16], photoconductive detectors [17] and antennas [18], UV photodetectors and gas sensors [19], solar cells [20][21][22] and solar heterojunctions [23], and light emitting diodes [24][25][26].…”
Section: Introductionmentioning
confidence: 99%